Understanding the concept of professionalisation in sport management research - Dowling, M.; Edwards, J.; Washington, M. (Sport Management Review, 2014)
It has been 80 years since the concept of professionalisation began to take root within the sociology and management disciplines. Similarly, the study of the professionalisation of sport has a relatively prominent and longstanding history within the discipline of sport management. Notwithstanding its continued usage and importance, there has been little systematic attempt to examine how the concept has been operationalised within sport management. In light of this recognition, this review piece draws upon extant sport management, sociological and managerial literature to (i) explore the various ways in which the concept of professionalisation has been employed within sport management, and in doing so, (ii) identifies potential research gaps and future avenues of inquiry within the sport management discipline. The review identifies three broad classifications of professionalisation (organisational, systemic, occupational) and calls for more research surrounding broader conceptualisations of professionalisation that remain relatively unexplored by sport management scholars.